2020
DOI: 10.1108/fs-07-2020-0069
|View full text |Cite
|
Sign up to set email alerts
|

Identifying future trends by podcast mining: an explorative approach for Web-based horizon scanning

Abstract: Purpose The aim of this paper is to gain knowledge in podcast mining as an additional source for Web-based horizon scanning (HS). The paper presents theoretical insights on the potential of podcast mining by exploring topics, which may be relevant in the future, and by reflecting the results against a background of HS approaches. The study provides a preliminary overview by presenting an exemplary list of podcast shows for further research. Design/methodology/approach The paper uses an exploratory quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Podcasts remain a potentially viable source of content to inform HS exercises, but at present remain a difficult medium to utilize. Whilst trials by Welz et al (2020) found that searches brought back relevant podcasts to their search requirements, in this case applied science, they did not manage to achieve the same level of results as other sources of data. As significant question remains, however.…”
Section: Looking Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…Podcasts remain a potentially viable source of content to inform HS exercises, but at present remain a difficult medium to utilize. Whilst trials by Welz et al (2020) found that searches brought back relevant podcasts to their search requirements, in this case applied science, they did not manage to achieve the same level of results as other sources of data. As significant question remains, however.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Welz et al (2020) have looked at broadening the possible scope of HS by seeing whether podcasts can likewise be used as a data source. Podcasts have become an increasingly popular way for individuals and organizations to discuss, promote, and analyze literally anything.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second phase, it was the aim to further develop, continue, and standardize the process by integrating AI and Big Data and thereby making use of (partly‐) automated processes. The efforts included (i) further optimizing an already well‐established tool for scanning structured data from scientific databases, (ii) exploring unstructured data sources to retrieve new Spotlights using News‐Sites and Podcasts (Welz et al, 2021), and (iii) identifying market potentials for Spotlights by analyzing corporate press releases via ML algorithms.…”
Section: The Hybrid Ai‐expert Foresight Approach In Practice: Insight...mentioning
confidence: 99%